Association Between Physical Activity Intensity and the Risk for Depression Among Adults From the National Health and Nutrition Examination Survey 2007–2018 - Yang, Donghui; Yang, Ming; Bai, Jianjun; Ma, Yudiyang; Yu, Chuanhua (Frontiers in Aging Neuroscience, 2022)
Objective Whether vigorous physical activities (VPA) bring additional benefits to depression prevention in comparison with moderate physical activity (MPA) remains unclear. The aim of this study was to find the correlation between the proportion of VPA to moderate-to-VPA (MVPA) (a combination of VPA and MPA) and the risk for depression, as well as to explore whether correlations differ among subgroups separated by age and sex. Methods The data originating from the National Health and Nutrition Examination Survey (NHANES) 2007–2018 were applied. The total amount of PA per week was obtained by multiplying frequency and duration. The proportion of VPA to MVPA was obtained among the participants who performed any MVPA. Depression was set for those who scored 10 and above in the Patient Health Questionnaire-9 (PHQ-9). The odds ratios (ORs) and 95% confidence intervals (95% CIs) for depression were evaluated using logistic regression. Results Among 26,849 participants of this study, only 12,939 adults were found with any MVPA, in which 748 participants with depression were detected. Logistic regression was conducted among 12,939 participants. The participants with higher than 66.7–100% of MVPA as VPA were inversely correlated with a 30% (OR = 0.70, 95% CI = 0.50, 0.99) lower risk for depression. The subgroup analyses revealed that significant correlations were only found in men and those aged 45 years and above. Conclusion This study suggested that a higher proportion of VPA to MVPA might be correlated with a lower risk for depression in men and those aged 45 years and above. Besides the recommendation, adults should perform 150 min MVPA per week, more time should be spent in performing VPA in MVPA among men and older adults.